Interactions of ErbB4 and Kap1 Connect the Growth Factor and DNA Damage Response Pathways - Gilmore-Hebert, Maureen (2010)
ErbB4 is unusual among receptor tyrosine kinases because some isoforms can be efficiently cleaved at the plasma membrane to release a soluble intracellular domain. The cleavage product has high kinase activity and homes to the nucleus. A screen for proteins that associate with the ErbB4 intracellular domain identified candidate interactors including ITCH, WWP2, Nucleolin, and Krab-associated protein 1 (Kap1). Kap1 binds to multiple isoforms of ErbB4 but does not require ErbB4 kinase activity for binding, nor is it an ErbB4 substrate. Kap1 reduces ERBB4 transcription and either directly or indirectly modulates the expression of genes that are themselves regulated by ErbB4. Upregulation of ErbB4 and suppression of MDM2 jointly enhance and accelerate the accumulation of p21(CIP1) in response to DNA damage. Overall, these findings further substantiate the role of ErbB4 in conjoint regulation of growth factor signaling and DNA damage responses.